Генераторы высоковольтных наносекундных импульсов: проспект - Воробьев А. А. Александр Акимович; Месяц Г. А. Геннадий Андреевич; Усов Ю. П. Юрий Петрович; Коршунов Г. С.; Хмыров В. В.; Ковальчук В. М.; Воробьёв П. А.; Поталицын Ю. Ф. (Томск, 1966)
В фонде НТБ ТПУ отсутствует